ANALYSIS OF THE POTENTIAL ACCEPTANCE OF ZAKAT PROFESSION WITH A NATURAL APPROACH - Agustina Br Surbakti; Syawal Harianto; Mizan Mizan; Nursyidah Nursyidah; Harjoni Desky (Faculty of Economics and Business, Universitas Malikussaleh, 2022)
Zakat is an obligation and a form of concern for others can be realized by helping those who are in distress, the way that can be taken to help is to distribute Zakat to the needy. This research aims to find out the potential of Zakat in Lhokseumawe State Polytechnic. This research uses descriptive research methods with a qualitative approach, which describes in detail the background, nature and specific or specific character of the observed subject (research subject). The study used primary and secondary data as a source of research. The results of this study concluded that the potential zakat profession from the basic salary of Lhokseumawe State Polytechnic employees in 2020, which was calculated from January to December 2020 using the assumption of Polytechnic employees according to the group that fulfills the obligation to pay zakat, namely group IV and III zakat obtained after the calculation of serdos, THR and salary 13 which is charged zakat at a rate of 2.5% amounting to Rp. 1,237,291,465 assuming that all employees who have fulfilled Criteria (Nisab) pays zakat.